1990
DOI: 10.1111/j.1476-5381.1990.tb14659.x
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of beraprost sodium, a new chemically stable prostacyclin analogue, against the deterioration of baroreceptor reflex following transient global cerebral ischaemia in dogs

Abstract: 1 A possible cerebroprotective effect of a chemically stable prostacyclin analogue, beraprost sodium, was investigated in a canine model of cerebral ischaemia. Cerebral ischaemia was produced by the combined occlusions of the left subclavian and the brachiocephalic arteries with preceding ligations of the intercostal arteries. 2 The decrease in baroreceptor reflex sensitivity (BRS), measured by phenylephrine-induced reflex bradycardia, following 5 min ischaemia was used to assess the cerebroprotective effect.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
2
5
0
Order By: Relevance
“…The effects of beraprost are similar to those of PGI, (Kovacs and O'Grady, 1984;Kainoh et al, 1990;Sakai et al, 1990). A cerebral cytoprotective effect of beraprost owing to the deterioration of the baroreceptor reflex following transient global cerebral ischemia in dogs was also reported (Kurihara et al, 1990). These data suggest that beraprost has protective effect on the cerebral ischemic damage.…”
Section: Discussionsupporting
confidence: 64%
“…The effects of beraprost are similar to those of PGI, (Kovacs and O'Grady, 1984;Kainoh et al, 1990;Sakai et al, 1990). A cerebral cytoprotective effect of beraprost owing to the deterioration of the baroreceptor reflex following transient global cerebral ischemia in dogs was also reported (Kurihara et al, 1990). These data suggest that beraprost has protective effect on the cerebral ischemic damage.…”
Section: Discussionsupporting
confidence: 64%
“…It is used for treatment and prevention of global cerebral ischemia in dogs and for cardiovascular diseases in humans (Kurihara et al, 1990; Murakami et al, 2005). In our study, one group of WT mice was pretreated with a single dose of vehicle (saline) or 50 or 100 μ g/kg beraprost per os (p.o.)…”
Section: Methodsmentioning
confidence: 99%
“…However, at least in a canine model of myocardial ischaemia, it has been shown that nicorandil failed to increase PGI2 release into coronary venous blood and that indomethacin failed to affect the cardioprotective effect of nicorandil (Gross et al, 1989). Furthermore, the protective effect of beraprost in our previous study (Kurihara et al, 1990a) was observed only at a dose higher than that required to inhibit platelet aggregation. Therefore, it seems to be unlikely that the cerebroprotective effect of nicorandil is due to an increase in PGI2 formation.…”
Section: Discussionmentioning
confidence: 55%
“…However, such a cytoprotective effect of nicorandil has yet to be established in organs other than the heart. In this context, the present study was conducted to investigate a possible cerebroprotective effect of nicorandil in a canine model of transient global cerebral ischaemia in which we have already confirmed the cerebroprotective effects of some drugs including flunarizine (Kurihara et al, 1989b;1990b), ifenprodil (Kurihara et al, 1990b), beraprost (Kurihara et al, 1990a) and halothane (Kurihara et al, 1992). The results were compared with those obtained with nitroglycerin and nicardipine.…”
Section: Introductionmentioning
confidence: 89%